2019
DOI: 10.1021/acs.iecr.9b04757
|View full text |Cite
|
Sign up to set email alerts
|

Alkaline Battery Separators with High Electrolyte Absorption from Forced Assembly Coextruded Composite Tapes

Abstract: In this work, two-component fibrous separators with high electrolyte absorption were fabricated by the delamination of oriented polymer tape which was produced using a unique coextrusion and multiplication process. Two different separators were created from polypropylene/high-density polyethylene (PP/HDPE) and polypropylene/polyamide 6 (PP/PA6) by this process. The separators have a pore size of 10 μm, high porosity, and high surface area. The electrolyte absorption (KOH uptake) of PP/HDPE separators and PP/PA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The benefits of this novel multilayering process includes flexibility, versatility, and precise control of the structural levels in addition to being solvent free and a continuous processing of materials 1,9 . The forced assembly multilayer coextrusion process enables many polymeric systems having unique architectures to be produced including multilayer films, 10 cellular film/foam materials, 11–14 and fibrous membrane systems 9,15–18 . In addition, there has been numerous studies on the multilayered coextruded polymer systems directed toward applications including gas barrier films, 8,19 optical films, 20 shape memory films, 21–24 packaging film/foams, 25 fibrous membranes for filtration, 18,26 antibacterial membranes, 27,28 cellular membranes having through pores 12 and multilayer films with unique dielectric properties 29–36 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The benefits of this novel multilayering process includes flexibility, versatility, and precise control of the structural levels in addition to being solvent free and a continuous processing of materials 1,9 . The forced assembly multilayer coextrusion process enables many polymeric systems having unique architectures to be produced including multilayer films, 10 cellular film/foam materials, 11–14 and fibrous membrane systems 9,15–18 . In addition, there has been numerous studies on the multilayered coextruded polymer systems directed toward applications including gas barrier films, 8,19 optical films, 20 shape memory films, 21–24 packaging film/foams, 25 fibrous membranes for filtration, 18,26 antibacterial membranes, 27,28 cellular membranes having through pores 12 and multilayer films with unique dielectric properties 29–36 .…”
Section: Introductionmentioning
confidence: 99%
“…1,9 The forced assembly multilayer coextrusion process enables many polymeric systems having unique architectures to be produced including multilayer films, 10 cellular film/foam materials, [11][12][13][14] and fibrous membrane systems. 9,[15][16][17][18] In addition, there has been numerous studies on the multilayered coextruded polymer systems directed toward applications including gas barrier films, 8,19 optical films, 20 shape memory films, [21][22][23][24] packaging film/foams, 25 fibrous membranes for filtration, 18,26 antibacterial membranes, 27,28 cellular membranes having through pores 12 and multilayer films with unique dielectric properties. [29][30][31][32][33][34][35][36] These investigations have emphasized the importance of scale within the multilayer films relative to enhanced performance characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…[ 30 ] Differential scanning calorimetry (DSC) analysis also revealed that the TFC membrane started to melt at ≈120 °C and exhibited a maximum melting peak at ≈140 °C, similar to that of the PE and HPE support membranes (Figure 2i). [ 31 ] The TGA and DSC results suggest that the TFC membrane has high thermal stability that can ensure stable operation without significant thermal deformation and/or decomposition at conventional AWE operating temperatures (<100 °C).…”
Section: Resultsmentioning
confidence: 99%